A subtraction scheme for massive QED - T. Engel; A. Signer; Y. Ulrich (Journal of High Energy Physics)
Abstract We present an extension of the FKS subtraction scheme beyond next-to-leading order to deal with soft singularities in fully differential calculations within QED with mas- sive fermions. After a detailed discussion of the next-to-next-to-leading order case, we show how to extend the scheme to even higher orders in perturbation theory. As an application we discuss the computation of the next-to-next-to-leading order QED corrections to the muon decay and present differential results with full electron mass dependence.